A região metropolitana do Rio de Janeiro na atualidade: recuperação econômica e reestruturação espacial - Oséias Teixeira Da Silva (Confins)
The present work aims to be a contribution to debate about metropolitan restructuring, talking as a reference to the analysis the metropolitan Region of Rio de Janeiro. The following describes the way we have travelled analytically from this objective: in the first part of work we are dedicated to understanding the origin and formation of metropolis and the metropolitan region highlighting the historical context in which it occurs, the characteristics that distinguish these areas of other and the meaning of them to the capitalist development; in the second part of the text we analyze the aspects of the process of metropolitan restructuring that has been occurring since the 1970s, highlighting two elements of this process, the metropolitan dispersion and the production of new metropolitan centralities; in the third part we seek to understand the characteristics of the occurrence of these two elements in the metropolitan region of Rio de Janeiro. Thus we assume the historical understanding of the formation of metropolis and metropolitan regions, through analysis of the restructuring process by which they pass from the decade of 1970, to finally understand this process from a specific reference: the metropolitan region of Rio de Janeiro.